Abatacept as a Long-Term Targeted Therapy for LRBA Deficiency - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (ELSEVIER, 2019)
BACKGROUND: LPS-responsive beige-like anchor (LRBA) deficiency presents with susceptibility to infections, autoimmunity, and lymphoproliferation. The long-term efficacy of cytotoxic T-lymphocyte-associated antigen 4-immunoglobulin (abatacept) as targeted therapy for its immune dysregulatory features remains to be established. OBJECTIVE: To determine the clinical and immunologic features of LRBA deficiency and long-term efficacy of abatacept treatment in controlling the different disease manifestations. METHODS: Twenty-two LRBA-deficient patients were recruited from different immunology centers and followed prospectively. Eighteen patients on abatacept were evaluated every 3 months for long-term clinical and immunologic responses. LRBA expression, lymphocyte subpopulations, and circulating T follicular helper cells were determined by flow cytometry. RESULTS: The mean age of the patients was 13.4 +/- 7.9 years, and the follow-up period was 3.4 +/- 2.3 years. Recurrent infections (n = 19 [86.4%]), immune dysregulation (n = 18 [81.8%]), and lymphoproliferation (n = 16 [72.7%]) were common clinical features. The long-term benefits of abatacept in 16 patients were demonstrated by complete control of lymphoproliferation and chronic diarrhea followed by immune dysregulation, most notably autoimmune cytopenias. Weekly or every other week administration of abatacept gave better disease control compared with every 4 weeks. There were no serious side effects related to the abatacept therapy. Circulating T follicular helper cell frequencies were found to be a reliable biomarker of disease activity, which decreased on abatacept therapy in most subjects. However, high circulating T follicular helper cell frequencies persisted in 2 patients who had a more severe disease phenotype that was relatively resistant to abatacept therapy. CONCLUSIONS: Long-term abatacept therapy is effective in most patients with LRBA deficiency. (C) 2019 American Academy of Allergy, Asthma & Immunology
Keywords: LPS-responsive beige-like anchor; Immune dysregulation; Abatacept; T follicular helper cells; Autoimmunity; IMMUNE DYSREGULATION; CTLA-4 CHECKPOINT; MUTATIONS; POLYENDOCRINOPATHY; ENTEROPATHY; DISEASE